Efeitos da suplementação com extrato de chá verde sobre biomarcadores de fadiga e desempenho neuromuscular - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The regular practice of intense physical exercise benefits health, but when the sessions are accomplished in consecutive day it migh intensify some deleterious effects of muscle fatigue, which can impair efficiency, promote muscle damage and increase injury risk. The interest in strategies to avoid or delay such effects, especially the oxidative stress, are desirable. In this regard, the green tea extract, from Camellia sinesis, can be useful due to its recognized antioxidant and antiinflamatory properties. Here our purpose was to determine whether the supplementation with green tea extract can benefit markers of muscle damage, oxidative stress and performance in exercise under fatigue. Sixteen male athletes trained were evaluted in cycling exercise under two conditions: without supplementation and without fatigue, and supplemented (placebo n=8; extrato de chá verde, n=8, 500 mg/dia durante 15 dias) and with fatigue (knee extension until exhaustion in two consecutive days). Blood 11 samples served to determine markers of muscle damage and oxidative stress. Electromyography was employed to monitore the muscle activation from vastus lateralis, as well as training parameters like heart rate, were quantified and compared between the groups and exercise conditions. Muscle activation did not differ between the cycling with and without fatigue in the green tea group, whereas in the placebo group there a loss of contractility due to fatigue. A higher cost observed by the higher heart rate support that reduction in the activation in the placebo group relies on the effort associated to the performance of the cycling exercise. Green tea supplementation was able to avoid increase in the muscle damage and oxidative stress in response to the exercise compared to the placebo group. Therefore, the properties of green tea seem to delay or avoid the muscle damage resultant of oxidative stress and preserves the contractility in athletes submitted to exercise under a fatigue state. As a conclusion, the supplementation with green tea can be considered a valid strategy in the physical training during extenuant tasks.
Effects of green tea extract supplementation on fatigue biomarkers and neuromuscular performance
Keywords: Camellia sinensis; Muscle damage; Endurance; Polyphenols; Oxidative stress; Camellia sinensis; Dano muscular; Endurance; Polifenois; Estresse oxidativo; CNPQ::CIENCIAS BIOLOGICAS